Organic carbon content and Fe-organo association in soils under rice dominant cropping system in Bangladesh - Biswas, Puja; Islam, Md Sanaul; Siddique, Abu Bakor; Halder, Milton (Bangladesh Journal of Botany, 2020)
Soil organic carbon (SOC) storage is significant for nutrient recycling and mitigation of greenhouse gasses emission from soil environment. It is investigated as to how SOC is varied and stored at iron (Fe) interface under different cropping systems. Thus, the experiment was conducted at three cropping systems consisted as Fallow-Fallow-Fallow (FL), Fallow - Fallow - Rice (OC), Fallow- Rice - Rice (TC). Soil samples were collected from the indicated cropping systems and three parameters were assessed: SOC, amorphous Fe oxides (Feo) and organically complex Fe (Fep) oxides. The results revealed that SOC content reduced significantly (p < 0.05) in the order of FL < OC < TC. Feo and Fep oxides also reduced significantly under OC and TC cropping systems compared to FL. A significant (p < 0.01) positive correlation between Feo and Fep oxides with SOC (r = 0.93, r = 0.86, respectively) was observed. The results suggest that Feo and Fep play a significant role to improve SOC storage through complex formation in soils of rice dominant cropping system.